Findings from the DUMA program: internet access, and frequency and nature of use among police detainees - Eileen Patterson
Examining access to and the extent of engagement with the Internet in illicit drug-using populations may provide an indication of the extent to which the online illicit drug market is usurping the physical illicit drug market, according to this report. Summary The advent of the Internet has created opportunities for the global exchange of information and purchase of goods and services. However, it has also facilitated the creation of online illicit drug markets and forums in which drug-related information can be exchanged between users. Bruno, Poesiat & Matthews (2013) reported that illicit drug-specific search terms (such as cocaine, ecstasy, hallucinogens and high) were used, on average, 39,700 times per month in the Google search engine in Australia. Examining access to and the extent of engagement with the Internet in illicit drug-using populations may provide an indication of the extent to which the online illicit drug market is usurping the physical illicit drug market. In 2006, Cunningham, Selby, Kypri & Humphreys examined Internet access in a sample of smokers, drinkers and illicit drug users (n=2,584) derived from the general population in Canada, through a random digit dialling technique. Restricting the findings to illicit drug users, 77 percent of cannabis users and 75 percent of cocaine users reported having Internet access. It would be anticipated that current Internet access rates would be considerably higher in all subgroups of the population, including illicit drug users, than those recorded in 2006